2019
DOI: 10.1128/iai.00826-18
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Endoplasmic Reticulum Stress Response Impacts the NOD1 Signaling Pathway

Abstract: Nucleotide-binding oligomerization domain 1 (NOD1) is an intracellular pattern recognition receptor (PRR) responsible for sensing bacterial peptidoglycan fragments. Stimulation of NOD1 leads to a robust innate immune response via activation of the major transcription factor NF-κB. In addition to peptidoglycan sensing, NOD1 and the closely related PRR NOD2 have been linked to inflammation by responding to the endoplasmic reticulum (ER) stress-induced unfolded protein response (UPR). Here we show that differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 55 publications
(72 reference statements)
0
27
0
1
Order By: Relevance
“…First, the interaction between TNF-α and the TNF-α receptor or between IL-1β and the IL-1 receptor can trigger the activation of NF-κB [36,55], which contributes to the upregulation of NOD1 and its adaptor RIP2. Second, endoplasmic reticulum (ER) stress, which can be initiated in response to TNF-α/IL-1β [56,57], was recently reported to contribute to the interaction of tumour necrosis factor (TNF) receptorassociated factor 2 (TRAF2) with NOD1 and lead to NOD1 activation [58,59]. However, the underlying mechanism by which TNF-α/IL-1β induced NOD1 and RIP2 upregulation at the molecular level remains to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…First, the interaction between TNF-α and the TNF-α receptor or between IL-1β and the IL-1 receptor can trigger the activation of NF-κB [36,55], which contributes to the upregulation of NOD1 and its adaptor RIP2. Second, endoplasmic reticulum (ER) stress, which can be initiated in response to TNF-α/IL-1β [56,57], was recently reported to contribute to the interaction of tumour necrosis factor (TNF) receptorassociated factor 2 (TRAF2) with NOD1 and lead to NOD1 activation [58,59]. However, the underlying mechanism by which TNF-α/IL-1β induced NOD1 and RIP2 upregulation at the molecular level remains to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…However, TLR engagement in itself can trigger ER stress through activation of XBP1, essential for production of inflammatory cytokines in macrophages ( 48 ). HLA-B27 misfolding was associated with enhanced replication of Salmonella by the activation of the unfolded protein response (UPR), through the transcription factor XBP1 ( 49 ) Although this study employs HeLa cells that do not express TLR, it is possible that innate immune receptors may be involved in response to bacteria or bacterial products ( 50 ). In another study, peripheral blood and serum polymerase chain reaction (PCR) analysis in patients with Chlamydia induced ReA showed the presence of DNA from C. trachomatis in the peripheral blood cells, but not in the serum ( 51 ).…”
Section: Putative Pathobionts In Hla-b27 Associated Spondyloarthropatmentioning
confidence: 99%
“…The link between NOD1 and ER stress appears to be the unfolded protein response, as inhibiting IRE1α, a kinase implicated in this pathway, attenuates the NOD1-associated inflammatory reaction ( 170 ). Some studies have associated ER stress with an imbalance in cellular Ca 2+ and the activation of NOD1 signaling ( 171 , 172 ). A recent study revealed that NOD1 activation both by bacterial pathogens and the NOD ligand C12-iE-DAP induced unfolded protein response activation through the ER kinase PERK, as well as Ca 2+ flux from the ER membrane Ca 2+ channel IP3R, which exacerbated the inflammatory response via NOD1 signaling ( 171 ).…”
Section: Nucleotide-binding Oligomerization Domain-like Receptorsmentioning
confidence: 99%
“…Some studies have associated ER stress with an imbalance in cellular Ca 2+ and the activation of NOD1 signaling ( 171 , 172 ). A recent study revealed that NOD1 activation both by bacterial pathogens and the NOD ligand C12-iE-DAP induced unfolded protein response activation through the ER kinase PERK, as well as Ca 2+ flux from the ER membrane Ca 2+ channel IP3R, which exacerbated the inflammatory response via NOD1 signaling ( 171 ). In the same line, Molinaro et al.…”
Section: Nucleotide-binding Oligomerization Domain-like Receptorsmentioning
confidence: 99%